Etnicidade e luta de classes na África contemporânea: Ruanda (1959 1994) e África do Sul (1948-1994) - Fonseca, Danilo Ferreira da (2013)
This thesis is mainly focused on the historical processes of South African apartheid and the Rwandan genocide of 1994, looking how occurred interactions, in the development of these, between different "ethnic racial" groups and social classes. Thus, in the case of South Africa, the thesis focuses on the years between 1948 (the beginning of the apartheid regime) and 1994 (end of apartheid and the election of Nelson Mandela), while in the Rwandan case the thesis focuses among years 1959 and 1994 (between independence and genocide in Rwanda in 1994). In order to understand the logic of specific social practices such territoriality, the thesis also rescues the pre-colonial and colonial period, valuing local traditions of many societies that permeate South Africa and Rwanda, giving support to understand how has built the preparation of their own local historical agents of a violent insertion of foreign capitalist mode of production. From these interactions between social practices and traditional practices tied to a capitalist society, the thesis structure the interaction between the "ethnic racial" and social classes that are formed and at the same time, help to form these societies that transform radically in a short time